Effectiveness of training physical therapists in pain neuroscience education for patients with chronic spine pain: a cluster-randomized trial. Issue 5 (5th May 2022) - Lane, Elizabeth; Magel, John S.; Thackeray, Anne; Greene, Tom; Fino, Nora F.; Puentedura, Emilio J.; Louw, Adriaan; Maddox, Daniel; Fritz, Julie M.
Abstract : Supplemental Digital Content is Available in the Text. In summary, pragmatic PT PNE training and delivery failed to produce significant functional changes in patients with chronic spinal pain but did produce significant improvement in pain self-efficacy over UC PT. Abstract: Chronic spinal pain poses complex challenges for health care around the world and is in need of effective interventions. Pain neuroscience education (PNE) is a promising intervention hypothesized to improve pain and disability by changing individuals' beliefs, perceptions, and expectations about pain. Pain neuroscience education has shown promise in small, controlled trials when implemented in tightly controlled situations. Exploration of promising interventions through more pragmatic methodologies is a crucial but understudied step towards improving outcomes in routine clinical care. The purpose was to examine the impact of pragmatic PNE training on clinical outcomes in patients with chronic spine pain. The cluster-randomized clinical trial took place in 45 outpatient physical therapist (PT) clinics. Participants included 108 physical therapists (45 clinics and 16 clusters) and 319 patients. Clusters of PT clinics were randomly assigned to either receive training in PNE or no intervention and continue with usual care (UC). We found no significant differences between groups for our primary outcome at 12 weeks, Patient-Reported Outcomes Measurement Information System Physical Function computer adaptive test mean difference = 1.05 (95% confidence interval [CI]: −0.73 to 2.83), P = 0.25. The PNE group demonstrated significant greater improvements in pain self-efficacy at 12 and 2 weeks compared with no intervention (mean difference = 3.65 [95% CI: 0.00-7.29], P = 0.049 and = 3.08 [95% CI: 0.07 to −6.09], P = 0.045, respectively). However, a similar percentage of participants in both control (41.1%) and treatment (44.4%) groups reported having received the treatment per fidelity question (yes or no to pain discussed as a perceived threat) at 2 weeks. Pragmatic PT PNE training and delivery failed to produce significant functional changes in patients with chronic spinal pain but did produce significant improvement in pain self-efficacy over UC PT.